Kajian Keberkesanan Penggunaan Bahan Fiber Polimer Sebagai Kotak Acuan Konkrit Berbanding Penggunaan Kotak Acuan Konvensional Di Tapak Bina - Mohd Rizal, Nisa Nabila; Abdul Rahman, Mohd Fahmi; Mustafa, Mohd Syafiq Syazwan (Progress in Engineering Application and Technology, 2023)
Concrete formwork is an element used in construction work. The use of plywood or wood is a traditional method that is usually used to make concrete moulds for building structure because they are easily available and do not use high costs. Nowadays, the use of other materials other than wood or plywood as concrete moulds on construction sites has been widely used, among which is the use of aluminium, fiberglass, plastic, steel and so on. In this study, the use of polymer fibre materials as concrete moulds inconstruction works can reduce the use of building materials such as wood or plywood. Concrete moulds that use polymer fibres materials can also be used repeatedly without having to worry about the surface of the mould being damaged and will damage the concrete surface. The purpose of this study is to examine the effectiveness of using polymer fibres materials as concrete moulds compared to wood or plywood used on construction sites while construction work is underway. The scope of this study has been limited to several construction company in Balakong, Selangor. The sample size required to analyse this study is expected to be 59 respondents from contractors. The data obtained from this study has been analysed using SPSS software and has obtained a mean range between 3.90 - 4.25. In conclusion, the results of this study can be measured.